Geographically dispersed ownership and inter-market stock price arbitrage—Ahold's crisis of corporate governance and its implications for global standards. - Clark, G; Wójcik, D; Bauer, R (Oxford University Press, 2006)
Scandals of corporate governance in the United States and Europe in the aftermath of the TMT bubble captured the public imagination. In play were the interests of senior executives in relation to investors, prompting debate over countries' standards of corporate governance in the global market place. Ahold was (and is) an especially important instance, involving significant internal accounting and reporting failures and poor public disclosure of market-sensitive information. Ahold is also a global corporation cross-listed on major financial markets. In this paper, we report the analysis of market trading in Ahold stock between Amsterdam and New York. It is shown that greater volatility in Amsterdam daily closing prices presaged the crisis to come in Ahold shares implying leakage of information to privileged local insiders. It is also shown that in the aftermath of Ahold's crisis, management responded to the lack of global investor confidence by improving transparency and governance standards consistent with the expectations of global investors. Implications are drawn for the pricing of corporate governance and the process of convergence in national standards of corporate governance. The continuity of different regimes of governance is subject to inter-market arbitrage especially if corporations seek to maintain and enhance their reputations in the global financial market place.